PENGARUH SIKAP KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI DI KLINIK IBU DAN ANAK AREA PONDOK JATI, SIDOARJO - Tatasari, Titis (Jurnal Riset Entrepreneurship, 2019)
This study aims to analyze the effect of transformational leadership on empowerment in employees of Pondok Jati Mother and Child Clinic, Sidoarjo analyzing the influence of transformational leadership on employee work behavior of Pondok Jati Mother and Child Clinic, Sidoarjo; The data analysis method uses Structural Equation Model (SEM). The results showed that transformational leadership had a significant and positive effect on the empowerment of employees at Pondok Jati Mother and Child Clinic, Sidoarjo, transformational leadership had a significant and positive effect on work behavior of Pondok Jati, Mother and Child Clinic employees, Sidoarjo, transformational leadership had no significant and influential effect on positively on the performance of employees of the Pondok Jati, Sidoarjo Mother and Child Clinic, empowerment has no significant effect and positively influences on the performance of the Pondok Jati, Sidoarjo Mother and Child employees, work behavior has a significant and positive effect on the performance of the Pondok Jati, Mother and Child Clinic employees, Sidoarjo.